Bizmart pending-sustainable food rack / Putra Faizurrahman Zahid ... [et al.] - Zahid, Putra Faizurrahman; Zulqernain, Nurul Syaqirah; Nik Hassan, Nik Suriati; Mohamed, Siti Sarah; Ismail, Zurina; Bustaman, Hasnun Anip (2022)
Basic social entrepreneurship concept applied in university environment to induce significant changes for community especially students in needs. Foods and drinks placed on open racks is made available from Bizmart UiTM Kelantan, placed strategically along student walkways in the student centre for students to purchase, or to buy on credit (partially or fully on credit), or simply take the food for free if they are in needs. The racks also serve as donation centre where anybody could contribute foods or money to buy foods. All the money collected from sales and donation will be used to repurchased foods and restock the rack for the next turnover.